The Use of Delayed Telephone Informed Consent for Observational Emergency Medicine Research Is Ethical and Effective. (16th April 2013) - Offerman, Steven R.; Nishijima, Daniel K.; Ballard, Dustin W.; Chetipally, Uli K.; Vinson, David R.; Holmes, James F.; Cone, David C.
Abstract Objectives The objective was to describe the rate of successful consent using an altered (deferred telephone) consent process in emergency department (ED) patients. Methods This study evaluated the consent process employed during a prospective, multicenter, observational study of outcomes in anticoagulated patients with blunt head trauma. The study was approved by the institutional review boards (IRBs) at all participating centers. Patients were not informed of the study during their enrollment at their index ED visit. Patient names, clinical findings, and contact information were collected at the time of initial ED visits. The patients or their legally designated surrogates were contacted by telephone at least 14 days after ED discharge, given all the elements of informed consent, and then consented for study participation. Study results are presented with simple descriptive statistics. Results A total of 506 patients with a mean (±SD) age of 75.8 (±12.2) years including 274 female subjects (54.2%; 95% confidence interval [CI] = 49.7% to 58.6%) were enrolled into the study. Patients or their surrogates were successfully contacted by telephone in 501 of 506 cases (99.0%; 95% CI = 97.7% to 99.7%). Consent was obtained in 500 of 501 cases at time of telephone follow‐up (99.8%; 95% CI = 98.9% to 100.0%). Surrogates provided consent in 199 cases (39.7%; 95% CI = 35.4% to 44.2%). Median time from ED visit to phone contact was 21 days (interquartile range [IQR] = 17 to 27 days). The median number of phone attempts for successful contact was 1 (IQR = 1 to 2 attempts). Conclusions The authors achieved a very high rate of successful telephone follow‐up in this predominantly older ED population. Obtaining consent to participate in a research study using a deferred telephone contact process was effective and well received by both subjects and surrogates. IRBs should consider deferred telephone consent for minimal‐risk studies requiring telephone follow‐up, as opposed to a consent process requiring written documentation at the time of initial ED visit.